Plasma-Based Dual-Band Reflective Surface - Magarotto, Mirko; Schenato, Luca; Santagiustina, Marco; Galtarossa, Andrea; Capobianco, Antonio-Daniele (IEEE access, 2023)
The subject of this work is the numerical design of a plasma-based dual-band reflective surface. The proposed concept consists of a series of cylindrical plasma discharges placed on top of a reconfigurable surface made of conventional metallic patches. The possibility to independently control the steering of two signals, one in Ku-band (12.5 GHz) and the other in Ka-band (27.5 GHz), with a frequency ratio larger than 2, is proven. The signal at a lower frequency is controlled via the plasma density, while the one at a higher frequency is reconfigured via the conventional metallic surface. Notably, the larger the difference between the two working frequencies, the more a plasma-based reflecting surface suits dual-band operations.